From the History of the Study of Old Believers in North-Western Belarus: Modern Period - Auseichyk, Uladzimir (Slavistica Vilnensis, 2023)
This article is the second part of the historiographical review of publications on the history, language and culture of the Old Believers of North-Western Belarus. It analyses the modern stage (1990–2000 years) of the study of this problematic. The review presents characteristics of both Belarusian and foreign (Lithuanian, Polish, Russian) historiography. The modern period is marked by the growing interest to the Old Believers in Belarus. As a result, a considerable volume of historical, ethnographic, linguistic and art history research has been published. A significant part of these studies is devoted to the Old Believer population of North-Western Belarus. The paper defines the main directions of scientific analysis of this problematic, characterizes methods and sources of the conducted research. We conclude that in spite of a rather significant volume of published researches, a number of important questions concerning the history, language and culture of Old Believers of North-Western Belarus have not been elaborated by now.
Keywords: Historiography; Old Believers; North-Western Belarus; Popular Culture; Folklore; Language